2018
DOI: 10.1038/s41418-018-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

A connexin43/YAP axis regulates astroglial-mesenchymal transition in hemoglobin induced astrocyte activation

Abstract: Reactive astrogliosis is a common response to insults to the central nervous system, but the mechanism remains unknown. In this study, we found the temporal and spatial differential expression of glial fibrillary acidic protein (GFAP) and Vimentin in the intracerebral hemorrhage (ICH) mouse brain, indicating that the de-differentiation and astroglial-mesenchymal transition (AMT) of astrocytes might be an early event in reactive astrogliosis. Further we verified the AMT finding in purified astrocyte cultures ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 56 publications
3
42
0
Order By: Relevance
“…Gap19 increases the activity of YAP in astrocytes after ICH injury in vitro A previous study showed that Cx43 may regulate YAP nuclear translocation in cultured astrocytes after hemoglobin stimulation [27]. Furthermore, YAP deletion has been demonstrated to lead to excessive activation of astrocytes during the development of the nervous system [28].…”
Section: Gap19 Reduces Astrocyte Activation and Astrocytic Proin Ammamentioning
confidence: 97%
“…Gap19 increases the activity of YAP in astrocytes after ICH injury in vitro A previous study showed that Cx43 may regulate YAP nuclear translocation in cultured astrocytes after hemoglobin stimulation [27]. Furthermore, YAP deletion has been demonstrated to lead to excessive activation of astrocytes during the development of the nervous system [28].…”
Section: Gap19 Reduces Astrocyte Activation and Astrocytic Proin Ammamentioning
confidence: 97%
“…Although previous studies have shown that reactive astrogliosis (also known as astrocyte activation) is necessary for poststroke CNS repair, recent studies have demonstrated that reactive astrogliosis plays a pivotal role in neurological injury in CNS injury models such as hemorrhagic stroke . Reactive astrogliosis is characterized by astrocyte hypertrophy and astrocyte proliferation, which have been shown to contribute to glial scar formation .…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have shown that reactive astrogliosis (also known as astrocyte activation) is necessary for poststroke CNS repair, [7][8][9] recent studies have demonstrated that reactive astrogliosis plays a pivotal role in neurological injury in CNS injury models such as hemorrhagic stroke. [10][11][12][13] Reactive astrogliosis is characterized by astrocyte hypertrophy and astrocyte proliferation, which have been shown to contribute to glial scar formation. 14 Despite glial scarring being necessary to seal the site of injury and protect damaged neural tissue, this repair mechanism inhibited the regrowth of damaged axons which contributed to further neurological deficits brought on by CNS injury.…”
Section: Introductionmentioning
confidence: 99%
“…Cx43 belongs to the integral membrane protein family called connexins which form hemichannels and gap junctions (GJs) that enable direct communication between neighbouring cells by interchanging electrical, metabolic and signalling molecules such as IP3, cAMP, ions, glutathione or siRNAs 19,20 . Additionally, these channel proteins act as scaffold proteins or signalling hubs via their cytoplasmic domains 4, 21 , regulating different key signalling pathways independently of their channel activity 4, [22][23][24] . Several Cx proteins are expressed in developing and mature skeletal tissues 19,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…During tissue regeneration and following injury, the dedifferentiation, redifferentiation and senescence processes play finely tuned temporal and spatial roles to reverse the loss of tissue in a precise way 35,36 . Cx43, via channel-dependent and -independent functions, has been involved in different phases of tissue regeneration including in controlling acute and chronic inflammation, cell differentiation, migration, proliferation or cellular reprogramming and lately in cellular senescence [22][23][24]37,38 . Results from our lab and others, demonstrated that Cx43 is a target of interest for the treatment of OA in order to stop cartilage degradation and to restore regeneration.…”
Section: Introductionmentioning
confidence: 99%